2006
DOI: 10.1161/01.hyp.0000242907.70697.5d
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-Dependent Angiotensin II Type 1 Receptor Signaling in Vascular Smooth Muscle

Abstract: A ngiotensin II (Ang II) is a pluripotent hormone in vascular smooth muscle cells (VSMCs) and stimulates arterial hypertrophy, a hallmark of remodeling in hypertension. These effects are mediated primarily through the G protein-coupled receptor Ang II type 1 receptor (AT 1 R). 1 In VSMCs, AT 1 R-mediated signaling is biphasic, and internalization of the agonist/receptor complex into what we called a "signaling domain" is required for the tonic phase of signaling (initially characterized by phospholipase D acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 82 publications
2
50
0
Order By: Relevance
“…As occurs with ERa, we found an association between both CAV-1 and CAV-3 and the MR. Furthermore, we demonstrated interactions between CAV-3 and AT 1 R, as has been reported (Ushio-Fukai & Alexander 2006), and between MR and AT 1 R. Both AT 1 R and MR were located in the membrane and cytoplasmic fractions, and immunoprecipitation studies revealed strong interactions between MR and AT 1 R in both fractions. These results suggest that the change in co-precipitation of AT 1 R and MR when sodium intake was restricted is likely to be occurring in both fractions.…”
Section: Discussionsupporting
confidence: 84%
“…As occurs with ERa, we found an association between both CAV-1 and CAV-3 and the MR. Furthermore, we demonstrated interactions between CAV-3 and AT 1 R, as has been reported (Ushio-Fukai & Alexander 2006), and between MR and AT 1 R. Both AT 1 R and MR were located in the membrane and cytoplasmic fractions, and immunoprecipitation studies revealed strong interactions between MR and AT 1 R in both fractions. These results suggest that the change in co-precipitation of AT 1 R and MR when sodium intake was restricted is likely to be occurring in both fractions.…”
Section: Discussionsupporting
confidence: 84%
“…In VSM, Cav-1 plays a role in the coupling of ␣-adrenergic, ANG II, and endothelin receptors to VSM contraction and growth (34,38,39,43). In the endothelium, Cav-1 anchors eNOS to caveolae, thus preventing its activation and reducing NO production and vascular relaxation (3,7,33).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the EGFR, relevant GPCRs (AT1, endothelin, β-adrenergic, muscarinic, opioid, adenosine), G proteins (α and βγ), Src family kinases, and ADAM17 have been reported to be, at least in part, localised to caveolae in non-cardiac cells (Smart et al, 1995;Mineo et al, 1996;Ushio-Fukai and Alexander, 2006;Takaguri et al, 2011).…”
Section: Cell Membrane Localisation -Membrane Rafts Caveolae and Cavmentioning
confidence: 99%